A "História dos sentimentos morais" e a Origem da justiça como equidade, em Humano, demasiado humano I, de Friedrich Nietzsche - Almeida, Diogo Heber Albino de (2016)
Within the philosophical production of Friedrich Nietzsche, the so-called First Period of his writing, is characterized by his researches on Nietzsche's critics to the excessive abuse of History and Historiography by the German state, in its construction as a new nation. As known, the thinker enterprises, at a later time, an appreciation of scientific knowledge said, in order to make it an evolution of the artistic man, and something liberating and joyful, easing the conflict between art and science. In HH 1, it is important to emphasize, Nietzsche proposes a historical research on moral, as part of a premise that is later called "revaluation". The "History", though, is thought to be something germinal to studies so-called "Genealogical", which will mark its last Period of his thought; and the work Human, All Too Human (1878) gets, at this point, invaluable relevance, as our object of study. The chapter "On the History of Moral Sensations", in HH, retains something exciting as a concept unexamined among the writings of Nietzsche, for the Middle Period. Within this topic, the term "justice" gets great importance in the studied chapter. Our study objected is, therefore, the matter of the "Origin of Justice as Fairness in Human, all too human 1", with its correlations, such as kindness, selfishness, revenge, pride, gratitude, grace... All these issues are intersect, certainly. Their problem lies precisely in leading the search for the "justice" ideas and "equality", that both are justified by these relationships. That's the relationship between "history" for Nietzsche with "moral sentiments", "moral values", "historical philosophy", "free spirit", "physio-psychology", "philosophical psychology", among others. The "justice" as social moral value, will meet elements that will give it some grounding.